A MORPHOLOGICAL ANALYSIS OF ENGLISH COMPOUND WORDS IN TOLSTOY’S GOD SEES THE TRUTH, BUT WAITS - Chusni Hadiati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2011)
Compounding is a process of word formation in a language (O’Grady, 1996). Compounding can be categorized into endocentric or exocentric. Endocentric is said to be more productive than exocentric (Katamba, 1994:320). Good Sees the Truth, but Waits is a short story employing a lot of compounding in its narration. Endocentric compounding found in the story is 60 comprising of compound verb (46), compound adjective (4) and compound noun (10). Each has its own elements which are: verb, noun, and preposition, adjective.